Analisis Peran Kepemimpinan Terhadap Kinerja Karyawan - Achmad Arifin (Universitas Kiai Abdullah Faqih Gresik, 2015)
This study aims to determine how much influence the leadership role has on employee performance at PT. Matahari Sakti Surabaya seen in terms of leadership. The results of this research analysis show that employee response to leadership attitudes is good, this is because employees who state that the leader's ability is very good with a score between 76 to 100 as many as 4 people, employees who state that the leader's ability is good with a score between 51 to 75 as many as 17 people, employees who state that the leader's ability is good enough with a score between 26 to 50 as many as 9 people, While employees who stated that the leader's ability was not good with a score of 25 did not exist. Performance of employees of PT. Matahari Sakti Surabaya shows very good performance, this is because employees have a total score of 16 to 20 which indicates a very good category of 11 people, employees have a total score of 11 to 15 which indicates a good category of 10 people, employees have a total score of 6 to 10 which indicates a fairly good category of 9 people, While employees have a total score of 5 which indicates a category of not good, none. The calculation results with the SPSS 16 method obtained the regression equation as follows: Y = -3.541 + 0.297x. The regression equation can be interpreted that the constant value (a) of -3.541 indicates that if the value of the leadership score is equal to zero in the sense of deviating from the wishes of employees, then employee performance is also very low with a total score of -3.541 and value (b) of 0.297 indicating that there is a positive relationship between leadership attitude and employee performance, so that if the leadership attitude is good, Then employee performance is also good and vice versa.